Ern’s and Golosovker’s Worlds of truth against the intellectual symbol of Immanuel Kant - Marchevsky, Ondrej (Ruch Filozoficzny, 2025)
The history of philosophy often shows that the legacy of the great philosophical thinkers is misunderstood, interpreted in a reductive way, and deliberately shifted in meaning. It also happens that their work is accepted as a threat worthy of elimination. The intellectual and geopolitical circumstances in Russia at the beginning of the 20th century created the background for the harsh criticism aimed at Kant. Its most radical manifestation was the work of the Neo-Slavophile Vladimir Frantsevich Ern, who compared Kant’s philosophy to the Krupp Werke artillery causing casualties on the battlefields of World War I. The nature of this critique becomes the subject of systematic treatment in this paper. It demonstrates that Kant becomes for Ern an intellectual symbol that serves the Russian thinker to deal with the age in which and for which he lived. At the same time, Ern’s approach is a particular expression of respect for the work of Kant. The explanatory framework of Kant as an intellectual symbol is a text-enhanced view of Y. E. Golosovker’s approach.